2020
DOI: 10.3390/ijms21134603
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous Expression of Dehydration-Inducible MfWRKY17 of Myrothamnus Flabellifolia Confers Drought and Salt Tolerance in Arabidopsis

Abstract: As the only woody resurrection plant, Myrothamnus flabellifolia has a strong tolerance to drought and can survive long-term in a desiccated environment. However, the molecular mechanisms related to the stress tolerance of M. flabellifolia are largely unknown, and few tolerance-related genes previously identified had been functionally characterized. WRKYs are a group of unique and complex plant transcription factors, and have reported functions in diverse biological processes, especially in the regulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 34 publications
(51 reference statements)
1
7
0
Order By: Relevance
“…A previous study reported that WRKY17 was involved in conferring stress tolerance in Arabidopsis [ 33 ]. Additionally, The WRKY transcription factors function as positive or negative regulators in salt and drought stress response in different species [ 23 , 34 ]. In the present study, overexpression of EjWRKY17 in Arabidopsis enhanced green cotyledons formation and root elongation under ABA treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous study reported that WRKY17 was involved in conferring stress tolerance in Arabidopsis [ 33 ]. Additionally, The WRKY transcription factors function as positive or negative regulators in salt and drought stress response in different species [ 23 , 34 ]. In the present study, overexpression of EjWRKY17 in Arabidopsis enhanced green cotyledons formation and root elongation under ABA treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The overexpression of GmWRKY16 in Arabidopsis resulted in a water loss rate and reduction of stomatal aperture under drought stress [ 29 ]. In a previous study, MfWRKY17 from Myrothamnus flabellifolia was confirmed as a positive regulator to mediate stomatal closure through an ABA-dependent signaling pathway [ 23 ]. Similarly, EjWRKY17 overexpression in Arabidopsis led to enhanced tolerance to ABA stress and promoted ABA-induced stomatal closure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The data demonstrated that MfWRKY7 overexpression effectively activated the antioxidant system in transgenic Arabidopsis lines to reduce the ROS-induced oxidative damage and maintain the dynamic balance of ROS, thereby improving tolerance to drought and salinity stresses. Previous studies showed that overexpressing CmWRKY10, SbWRKY30, or MfWRKY17 could enhance the activities of antioxidant enzymes and hence stress tolerance [ 44 , 45 , 46 ]. Therefore, strengthening the antioxidant system might be a generally common strategy of WRKY TFs to increase plant’s tolerance to abiotic stress.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that overexpression of WRKY transcription factors induces the accumulation of ABA under abiotic stress ( Ma et al, 2019 ; Dong et al, 2020 ). Furthermore, the ABA-responsive genes are significantly up-regulated in plants overexpressing WRKYs under drought and salt stress, indicating that WRKY regulates drought and salt tolerance of plants through ABA regulatory pathway ( Dong et al, 2020 ; Huang et al, 2020 ). Conversely, ABA also induces the expression of WRKYs to mediate stress tolerance.…”
Section: Discussionmentioning
confidence: 99%